A category contingent aftereffect for faces labelled with different religious affiliation is seen 7 days after adaptation. (May 2023) - Foglia, Victoria; Rutherford, M.D.
Visual adaptation occurs after a prolonged exposure to a stimulus. The duration of aftereffects differs across stimuli type, and face aftereffects may be especially long lasting. The current study investigates adaptation decay of category contingent opposing aftereffects. Specifically, we tested whether naïve undergraduate participants' adaptation to photos of faces with explicit religious labels, differed from that of participants who had adapted to the same faces 7 days previously. We also tested whether 7-day old category-contingent opposing aftereffects interfere with the ability to re-adapt to a new condition. In Session 1, undergraduates made attractiveness preference selections before and after adapting to two groups of distorted faces. Participants then returned 7 days later to re-assess the attractiveness of the same faces. Participants were then adapted to the two groups of faces distorted in the opposite direction. Adaptation strength was stronger in Session 1 than in Session 2, although adaptation strength was not related to pre-adaptation selections. Week-old aftereffects interfered with the creation of aftereffects in the opposite direction 7 days later.